(untitled) (Praxis Educativa, 2025)
This dossier, entitled "Toward New Scenarios in Higher Education: Challenges and Opportunities in the Age of Artificial Intelligence," seeks to bring together reflections and experiences on the role of AI in higher education, with the goal of thoroughly understanding the transformations this technology is generating in the field of education. In Argentina, as in other countries, the discussion about AI in higher education addresses multiple dimensions: accessibility, equity, digital skills training, and the establishment of ethical frameworks that guarantee the responsible use of these technologies. Thus, we want to explore how artificial intelligence is reshaping the teaching and learning experience, from the way content is reorganized and the dynamics between teachers and students to the ways in which knowledge is constructed in university spaces. Along the same lines, our interest lies in finding alternatives that technology offers in terms of providing access and cultivating key skills, while taking into account the methodological and ethical tensions resulting from its use. We seek to promote a critical analysis of the opportunities that intelligent systems offer to improve accessibility and foster essential digital skills in students, as well as the ethical, pedagogical, and methodological challenges they present.